290 Are obstetrics and gynaecology trainees confident and competent in the care of frail gynaecological oncology patients?. (13th November 2020) - Owens, G; Sivalingam, V; Bharathan, R; Abdelrahman, M; Beirne, J; Blake, D; Collins, A; Davies, R; Dilley, J; Farquharson, M; Frimpong, D; Gomes, N; et al.
Abstract : Introduction: Older patients undergoing cancer surgery are at increased risk of post-operative morbidity and mortality. Frailty is particularly prevalent in this patient cohort and is a major contributor to adverse outcomes. A survey was conducted to assess the confidence and knowledge of trainees in obstetrics and gynaecology (O&G) regarding identification and management of perioperative issues encountered in frail gynaecological oncology patients. Methods: A web-based survey on the management of frail perioperative patients was disseminated to doctors-in-training (trainees) in O& G in the United Kingdom (UK) and Ireland. Results: Of the 666 trainees who participated, 67% (n=425/666) reported inadequate training in the perioperative management of frail patients. Validated frailty assessment tools were used by only 9% (n=59/638) of trainees and less than 1% (n=4/613) were able to correctly identify the diagnostic features of frailty. Common misconceptions included the use of chronological age and gender in frailty assessments. The majority trainees (>75%) correctly answered a series of questions relating to mental capacity; however, only 6% (n=36/606) were able to correctly identify all three diagnostic features of delirium. 87% (n=495/571) of trainees supported closer collaboration with geriatricians and a multi-disciplinary approach. Conclusions: O&G trainees reported inadequate training in the perioperative care of frail gynaecological oncology patients, and overwhelmingly favoured input from geriatricians. Routine use of validated frailty assessment tools may aid diagnosis of frailty in the perioperative setting. There is an unmet need for formal education in the management of frail surgical patients within the UK and Irish O&G curriculum.